INTERCHANGEABILITY OF MYOCARDIAL CYTOPROTECTORS IN PATIENTS WITH ISCHEMIC HEART DISEASE. DIFFICULT QUESTIONS –SIMPLE SOLUTIONS - Zh. M. Sizova (Рациональная фармакотерапия в кардиологии)
Indications for myocardial cytoprotector, trimetazidine, in patients with ischemic heart disease are analyzed and justified according to evidence based medicine. Results of a multicenter randomized comparative KARDIOKANON study are discussed in terms of efficacy and tolerability of two variants of the complex 12-week treatment in patients with angina II-III functional class, based on the original and generic drugs. The study showed clinical equivalence of the generic DeprenormR (Canonpharma Production) to the original trimetazidine.